(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
It was observed that rhizome extract of Zingiber officinale A. juss possesses antifungal properties and it reduced the radial growth of Neurospora crassa Ema. After treating conidia of Ema with rhizome extract of Z. officinale, 10 groups of mutants were found i.e. albino, fluffy, fluffy-band, yellow-fluffy, crescent, checked, conidial band, ropy, plug and vigorous. Key words: Neurospora crassa, Zingiber officinale, Mutants, Albino, fluffy, Fluffyband, Yellow-fluffy, Crescent, Checked, Conidial band, Ropy, Plug and Vigorous. DOI: 10.3329.bjsir.v43i1.862 Bangladesh J. Sci. Ind. Res. 43(1), 117-122, 2008